In vivo study of the pharmacokinetic effect of amlodipine and gliclazide - Helal Uddin, A.B.M.; Alaama, Mohammed; Awang, Mohamed; Abbas, Syed Atif (Centre of Lipids Engineering and Applied Research (CLEAR), Universiti Teknologi Malaysia (UTM), 2017)
It was found that there is kind of pharmacodynamic interaction between calcium channels blockers and sulfonylurea. The addition of amlodipine (AMLO) to gliclazide (GLZ) course caused significant decrease in glucose lowering effect of GLZ. The mechanism of AMLO-GLZ interaction is not well understood. There is a possibility that this interaction can be a result of pharmacokinetic interaction of both drugs; therefore, this study was designed to investigate the pharmacokinetic interaction between AMLO and GLZ in animal model. The pharmacokinetic interaction was evaluated using Sprauge Dawly rates as they were divided into three groups. The controle group received saline and the gliclazide groupe received gliclazide orally in the dose of 1.44 mg/kg, while the Amlo-Gliclazide groupe has received amlodipine and gliclazide orally with a dose of 0.09 mg/kg and 1.44 mg/kg respectively. After dosing, animals were anesthetized and the blood was collected using retro orbital blood collection method after 1, 2, 4, 6, 8, 12, 24 hours of the dose. A new and novel LC-MS/MS method was developed and validated for the determination of GLZ in and rat plasma. The results showed that the pharmacokinetic parameters such as Cmax (ng/ml), Tmax (hr) were not altered significantly by AMLO administration. However, the administration of AMLO lead to significant increase (p = 0.000672) in AUC. In conclusion the plasma GLZ concentration increased when it was co administered with AMLO, while Cmax and Tmax remain unchanged. This study suggests that AMLO might reduce GLZ elimination.